Evaluation of obstetric outcomes in Brazilian pregnant women with Takayasu arteritis - Marcela Ignacchiti Lacerda Ávila; Marcela Gaiotti Marques; Maria Eduarda Araújo Machado da Rocha; Flávia Cunha dos Santos; Manuella Lima Gomes Ochtrop; Nilson Ramires de Jesús; Guilherme Ribeiro Ramires de Jesús; Camila Souto Oliveira Elias (Advances in Rheumatology, 2023)
Abstract Objective Takayasu arteritis (TAK) is a rare chronic granulomatous vasculitis that affects large vessels and usually begins in women of childbearing age, so it is not uncommon for pregnancies to occur in these patients. However, there is limited information about these pregnancies, with reports of adverse maternal and obstetric outcomes. The objective of this study is to evaluate adverse maternal, fetal and neonatal events in pregnant patients with TA. Methods This is a cross-sectional study with retrospective data collection. We reviewed 22 pregnancies in 18 patients with TAK, according to the American College of Rheumatology criteria, that were followed up in a high-risk prenatal clinic specialized in systemic autoimmune diseases and thrombophilia (PrAT) at Hospital Universitário Pedro Ernesto, from 1998 to 2021. Results In twenty-two pregnancies, the mean age of patients was 28.09 years and the mean duration disease was 10.9 years. Of the 18 patients with TAK studied, only one had the diagnosis during pregnancy and had active disease. All other patients had a previous diagnosis of TAK and only 3 had disease activity during pregnancy. Twelve patients (66.6%) had previous systemic arterial hypertension and eleven (61.1%) had renal involvement. Among maternal complications, eight patients (36.3%) developed preeclampsia and six (27.2%) had uncontrolled blood pressure without proteinuria, while 10 (45%) had puerperal complications. Four (18.1%) births were premature, all due to severe preeclampsia and eight newborns (34.7%) were small for gestational age. When all maternal and fetal/neonatal outcomes included in this study were considered, only 6 (27.2%) pregnancies were uneventful. Conclusion Although there were no maternal deaths or pregnancy losses in this study, the number of adverse events was considerably high. Hypertensive disorders and small for gestational age newborns were more common than general population, while the number of patients with active disease was low. These findings suggest that pregnancies in patients with TAK still have several complications and a high-risk prenatal care and delivery are necessary for these patients.